2023
DOI: 10.11591/ijece.v13i3.pp3299-3310
|View full text |Cite
|
Sign up to set email alerts
|

Slum image detection and localization using transfer learning: a case study in Northern Morocco

Abstract: <span lang="EN-US">Developing countries are faced with social and economic challenges, including the emergence and proliferation of slums. Slum detection and localization methods typically rely on regular topographic surveys or on visual identification of high-resolution spatial satellite images, as well as socio-environmental surveys from land surveys and general population censuses. Yet, they consume so much time and effort. To overcome these problems, this paper exploits well-known seven pretrained mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Through harnessing this pre-training, the model can be fine-tuned or employed as a feature extractor for a range of computer vision assignments, including image classification, object detection, and image segmentation [29], [30]. There are several CNN-based methods that are widely used for various applications [31]- [33], but in this study, we focus on ResNet50. We will include other deep learning methods on future work agendas.…”
Section: Methodsmentioning
confidence: 99%
“…Through harnessing this pre-training, the model can be fine-tuned or employed as a feature extractor for a range of computer vision assignments, including image classification, object detection, and image segmentation [29], [30]. There are several CNN-based methods that are widely used for various applications [31]- [33], but in this study, we focus on ResNet50. We will include other deep learning methods on future work agendas.…”
Section: Methodsmentioning
confidence: 99%
“…DL models automatically extract discriminative high-level semantic features without the need for complex feature engineering of the input data [25], outperforming previous techniques in the capacity to extract information. Studies [29][30][31][32][33] on slum mapping based on DL have also generated fine results. Wurm M. et al [29] employed a fully convolutional neural network (FCN) to extract slums and obtained an overall accuracy (OA) of 90.64% on Quick Bird images with a resolution of 2 m and an OA of 86.71% on Sentinel-2 images with a resolution of 10 m. Wurm M.'s study demonstrated the advancement of DL on slum mapping.…”
Section: Introductionmentioning
confidence: 99%